2014
DOI: 10.5761/atcs.cr.13-00092
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Experience of Symptomatic Sigmoid Septum: Drastic Exacerbation of Mitral Regurgitation after Sufficient Ventricular Septal Myectomy

Abstract: A 74-year-old woman presented with progressive dyspnea on exertion. Transthoracic echocardiography (TTE) demonstrated significant left ventricular outflow tract (LVOT) obstruction with a pressure gradient of 100 mmHg caused by a sigmoid septum (SS). Mitral regurgitation (MR) of a mild to moderate degree occurred due to systolic anterior motion (SAM) of the anterior mitral leaflet (AML), with no intrinsic mitral valve (MV) abnormality. Myectomy of the hypertrophied septal bulge ameliorated the pressure gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Belenkie et al ( 6 ) reported that an autopsy performed in one patient with localized septal hypertrophy and without SAM showed no fiber disarray. In addition, according to Fujita et al ( 7 ), a specimen of the resected septum in sigmoid septum with LVOTO showed only slight myocardial disarray, which was not compatible with HCM. In the present case, HCM was completely ruled out as a cause of basal septal bulge based on the autopsy findings.…”
Section: Discussionmentioning
confidence: 94%
“…Belenkie et al ( 6 ) reported that an autopsy performed in one patient with localized septal hypertrophy and without SAM showed no fiber disarray. In addition, according to Fujita et al ( 7 ), a specimen of the resected septum in sigmoid septum with LVOTO showed only slight myocardial disarray, which was not compatible with HCM. In the present case, HCM was completely ruled out as a cause of basal septal bulge based on the autopsy findings.…”
Section: Discussionmentioning
confidence: 94%
“…Accumulating evidence suggests that mitral valve abnormalities can be critically involved in LVOTO in HCM. [29][30][31][32][33][34][35][36] Alhaj et al 35 thickness measurement method such that "the actual tissue-blood interface, rather than the distance between the leading edge echoes," be utilized.…”
Section: Bsh In Hcm Literaturementioning
confidence: 99%
“…Accumulating evidence suggests that mitral valve abnormalities can be critically involved in LVOTO in HCM . Alhaj et al .…”
Section: Bsh In Hcm Literaturementioning
confidence: 99%
“…Although the mechanisms of SAM and LVOTO are partly the same as that of HOCM and isolated muscle resection could be sufficient, deterioration of MR after myectomy has been reported. 7 Fujita et al reported a patient with SAM and LVOTO due to sigmoid septum and normal mitral valve pathology who presented with severe MR just after myectomy. 7 The mitral valve had to be finally replaced in this case.…”
Section: Sam and Lvoto In Patients With Sigmoid Septummentioning
confidence: 99%
“…6 There exists a report about a failure, that is, exacerbation of mitral regurgitation (MR) after isolated myectomy for SAM and left ventricular outflow tract obstruction (LVOTO) in sigmoid septum with relatively thin interventricular septum. 7 The authors speculated that abnormal papillary muscle attachment might have caused the failure. We believe that the effect of isolated myectomy is limited when the interventricular septum is relatively thin (<20 mm), we employed mitral valve repair concomitant with myectomy for HOCM cases with SAM and LVOTO when MR is more than mild.…”
Section: Introductionmentioning
confidence: 99%